Effect of Spectral Variability of Aerosol Optical Properties on Direct Aerosol Radiative Effect - Kato, Seiji; Thorsen, Tyler J.; Ham, Seung-Hee; Loeb, Norman G.; Ferrare, Richard A.; Winker, David M.; Barker, Howard; Stephens, Graeme L.; Schmidt, Sebastian; Meyer, Kerry G.; Cairns, Brian (Frontiers in Remote Sensing, 2022)
Aerosol optical properties depend on wavelength as well as both mixing ratios and size distributions of components that make up a particular type of aerosol. This study examines impacts on direct aerosol radiative effect (DARE) for desert, clean maritime, and polluted maritime aerosol types over ocean when their optical properties are determined by various combinations of observations made by active (i.e., lidar) and passive (e.g., shortwave spectrometer) satellite sensors. Spectral optical properties are perturbed by altering mixing ratios of components that define aerosol types with assumptions that components within an aerosol type are fixed and only one aerosol type is present in the atmosphere. When 532 nm depolarization ratio from the lidar is used to identify desert aerosol, the uncertainty in the mean DARE due to spectral optical property variabilities is 10%. When 532 nm depolarization and lidar ratios are used to identify clean and polluted maritime aerosols, uncertainties in mean DARE are, respectively, 4% and 18%. When scattering optical thicknesses are also known to within 3% at four passive imager wavelengths (340 nm, 546 nm, 966 nm, and 1657 nm), uncertainty in the polluted maritime DARE decreases to 8%. Uncertainties in the instantaneous top-of-atmosphere (TOA) reflected irradiances derived from observed broadband radiances and angular distribution models are also estimated. When TOA irradiances are derived solely from the nadir viewing, their uncertainties can be reduced if aerosol type can be both identified and aerosol type dependence is considered in the radiance to irradiance conversion. This is especially so for aerosols with large fraction of nonspherical particles, such as desert aerosols.